'Rhetor', 'rex': la retórica como instrumento rector de la sociedad en los "Institutionum rhetoricarum libri III" (1554) de Fadrique Furio Ceriol - Teodoro Peris, Josep Lluís (Ágora: estudos clássicos em debate, 2018)
Fadrique Furio Ceriol conceives rhetoric as an instrument of dialogue in a context of deep social, economic and philosophical change, accompanied by armed conflicts where the conflicting political, religious and moral conceptions of the peoples of Europe become evident. Dialogue and persuasion are the basis of understanding and the author makes its use extensive to all social strata without exception, thereby displaying a view of society that contrasts with the rising royal authoritarianism of his time.